Damage mode and load distribution of countersunk bolted composite joints. (June 2021) - Ge, Mingming; Cheng, Xiaoquan; Huang, Wenjun; Hu, Renwei; Cheng, Yujia
Tensile experiments were conducted with single-bolted and multi-bolted countersunk composite-metal joints. The finite element models with Hashin criteria and modified Camanho degradation law were developed to predict the bearing load and to simulate the failure behavior. The models were validated with the experimental results, including load-displacement curves and composite damage profiles. Based on the verified models, bolt load distributions of multi-bolted joints were calculated and analyzed before and after damage occurs. Results show that composite damages can change the bolt load distributions to a certain extent, which needs to be considered during the structure design. To adjust the bolt load distribution, the effects of joint variables, including bolt-hole clearance, bolt spacing, countersunk height ratio, and bolt stiffness combination, have been studied. It is found that the increase of the pin clearance around the largest bearing bolt would decrease its corresponding bearing load. The countersunk height ratio affects the bolt load distribution difference that a greater ratio leads to a less difference. The bolt spacing and bolt stiffness can also be used to reduce the bolt load distribution difference with elaborately designed combinations.